The Application of the Tsulusi Muroja'ah Method in Improving the Fluency of Qur'an Memorization Among Students at Madinatul Qur'an Umbul Lumajang Islamic Boarding School - Abdul Rouf Al-Majid; Mochamad Samsul Arifin (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The purpose of this research is to analyze the use of the Muroja'ah Tsulusi method in improving the fluency of Quran memorization among students at Pondok Pesantren Madinatul Qur'an, Umbul Lumajang. The method used in this research is descriptive qualitative. The data collection process involved observation, comprehensive interviews, and documentation gathered from the administrators of the Islamic boarding school, the hafiz/hafizah mentors, and the students of the hafiz program. The Tsulusi Muroja'ah method is considered effective because it applies a structured pattern of memorization repetition compared to the general muroja'ah method, thus it is deemed capable of helping balance the addition and maintenance of memorization. Data analysis was conducted thru the stages of data reduction, data presentation, and conclusion. The validity test was conducted using source and technique triangulation. The research results prove that the Muroja'ah Tsulutsi method has a positive impact on the memorization ability of the Qur'an among the students, with improvements in the fluency of memorization, reading accuracy, and the ability to recall memorized verses. Systematic repetition of memorization minimizes pronunciation errors, maintains memorization, and enhances self-confidence during memorization. The improvement of a disciplined study attitude is stimulated thru regular muroja’ah. The Tsulusi Muroja'ah method has the potential to improve the fluency and quality of Quran memorization among students in the pesantren environment.